2020
DOI: 10.1371/journal.pone.0226977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with a microalga (Schizochytrium sp.) on the hemato-immunological, and intestinal histological parameters and gut microbiota of Nile tilapia in net cages

Abstract: Nutritional improvements in intensive aquaculture production systems is necessary for the reduction of stress, maximum utilization of nutritional components, and expression of the genetic potential of fish. The objective of this study was to evaluate the hemato-immunological, and histological parameters and gut microbiota of Nile tilapia fed with the microalga Schizochytrium sp. Males of Nile tilapia were distributed among eight net cages (6 m 3 ), and fed for 105 days with two diets: control (CON), without Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 59 publications
(90 reference statements)
6
41
3
Order By: Relevance
“…The feeding of supplemented diets increased microbial diversity and thus affected species composition in the zebrafish gut. A similar increase in diversity of gut bacteria has been reported in studies with tilapia (Oreochromis niloticus) and rainbow trout (Oncorhynchus mykiss) fed a whole-cell dietary Schizochytrium meal [35,58]. The increase in diversity in the present study could be an adaption to enable digestion and assimilation of the added microalga-derived ingredients, including cell-wall components, polysaccharides, and lipids with omega-6 LC-PUFA (DGLA or ARA), substrates that may have attracted colonization by relatively less abundant (rare) bacterial taxa, in addition to the previously colonized microbiota.…”
Section: Microalgal Diets Modulate Gut Health and Infection Outcome Tsupporting
confidence: 79%
See 2 more Smart Citations
“…The feeding of supplemented diets increased microbial diversity and thus affected species composition in the zebrafish gut. A similar increase in diversity of gut bacteria has been reported in studies with tilapia (Oreochromis niloticus) and rainbow trout (Oncorhynchus mykiss) fed a whole-cell dietary Schizochytrium meal [35,58]. The increase in diversity in the present study could be an adaption to enable digestion and assimilation of the added microalga-derived ingredients, including cell-wall components, polysaccharides, and lipids with omega-6 LC-PUFA (DGLA or ARA), substrates that may have attracted colonization by relatively less abundant (rare) bacterial taxa, in addition to the previously colonized microbiota.…”
Section: Microalgal Diets Modulate Gut Health and Infection Outcome Tsupporting
confidence: 79%
“…Studies on the effects of microalga-supplemented diets on the host microbiome are very rare. Previous studies analyzing fish microbiome alterations in response to dietary fatty acid supplementation used mainly omega-3 LC-PUFA-producing microorganisms, such as Schizochytrium [35], and the microalgae Nannochloropsis gaditana [34] and Phaeodactylum tricornutum [33]. This is the first report of the effects of omega-6 LC-PUFA-rich L. incisa on the fish gut microbiome.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Similar results were found in Nile tilapia (Oreochromis niloticus) fed a diet supplemented with 1.2% of Schyzochytrium sp. [87]. In both former studies, dietary changes on microbiome diversity did not result in changes on the microbial community structure.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, the polyunsaturated fatty acids (PUFAs) from Schizochytrium modulate lymphocyte function by targeting plasma membrane molecular organization such as physical properties (compressibility, phospholipid flip-flop, acyl chain packing, elasticity) and chemical properties (lipid domain formation) [ 126 ]. The polyunsaturated fatty acids from Schizochytrium induce microbiota stimulation and mucin release [ 97 ]. In recent studies, it was demonstrated how PUFAs disrupt membrane domain organization through changes in lipid rafts activating specific signalling networks through the microbiota stimulation and cytokines release [ 127 ], and anti-inflammatory activities [ 128 ].…”
Section: Marine Microalgal Compounds Inducing Icd In Cancer Cellsmentioning
confidence: 99%